2020
DOI: 10.1021/acs.est.0c00228
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Legacy Perfluoroalkyl Substances and the Replacement Compound HFPO-DA through the Atlantic Gateway to the Arctic Ocean—Is the Arctic a Sink or a Source?

Abstract: The spatial distribution of 29 per- and polyfluoroalkyl substances (PFASs) in seawater was investigated along a sampling transect from Europe to the Arctic and two transects within Fram Strait, located between Greenland and Svalbard, in the summer of 2018. Hexafluoropropylene oxide-dimer acid (HFPO-DA), a replacement compound for perfluorooctanoic acid (PFOA), was detected in Arctic seawater for the first time. This provides evidence for its long-range transport to remote areas. The total PFAS concentration wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 55 publications
(97 reference statements)
6
66
3
Order By: Relevance
“…We found that with the increase of PAH molecular weight, the net mass flux to the Arctic Ocean increased. Previous studies reveal similar trends for PFAS, as a net outflow for shorter‐chain PFASs and HCHs, while a net inflow for the PFASs with ≥eight perfluorinated carbons or high‐molecule‐weighted PCBs (Joerss et al., 2020; Y. Ma et al., 2018).…”
Section: Resultsmentioning
confidence: 57%
“…We found that with the increase of PAH molecular weight, the net mass flux to the Arctic Ocean increased. Previous studies reveal similar trends for PFAS, as a net outflow for shorter‐chain PFASs and HCHs, while a net inflow for the PFASs with ≥eight perfluorinated carbons or high‐molecule‐weighted PCBs (Joerss et al., 2020; Y. Ma et al., 2018).…”
Section: Resultsmentioning
confidence: 57%
“…The concentration gradient of HFPO-DA in ocean water decreased with increasing distance from the European coastline, suggesting that emissions from European waters are likely the primary source of this compound. However, mass transport profiles for other PFAS suggested that long-range atmospheric deposition contributes significantly to legacy PFAS in Arctic outflow [75]. This study demonstrated for the first time the long-range transport of HFPO-DA to remote regions.…”
Section: Long-range Transportmentioning
confidence: 71%
“…Compared with levels near FPPs, environmental concentrations of emerging PFAS distant from direct emission sources remain relatively low, indicating emissions from fluorochemical manufacturing are primarily responsible for the presence of these compounds in the environment. Still, the detection of emerging alternatives such as HFPO-DA [75] in remote regions suggests that despite relatively limited production history, many of these alternatives are, or have the potential to become, global contaminants.…”
Section: Sources Of Emerging Pfasmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, PFAS are detected in trace concentrations worldwide in biological and environmental matrices, even at remote and pristine locations [ 7 , 8 , 9 ]. To date, several bioanalytical methods are available for the determination of PFAS in a variety of biological matrices, and liquid chromatography–tandem mass spectrometry (LC-MS/MS) is currently the main instrumental technique applied for their analysis, achieving low limits of detection that can reach the picogram range [ 10 ].…”
Section: Introductionmentioning
confidence: 99%